PENGARUH PENAMBAHAN BERBAGAI STARTER PADA PEMBUATAN SILASE RANSUM TERHADAP KADAR SERAT KASAR, LEMAK KASAR, KADAR AIR, DAN BAHAN EKSTRAK TANPA NITROGEN SILASE - Istiana Pratiwi; Farida Fathul; Muhtarudin . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of this research are to find: 1) the effects of addition of various kind levels of starter to crude fiber, crude fat, moisture content, extract material without nitrogen, in silage feed, 2) one of the best starter in increasing the nutrient content in silage feed. The research was conducted in December 2014 – Februari 2015 at Department of Animal Husbandry, Faculty of Agriculture, University of Lampung and in the Laboratory of Nutrition and Feed Livestock, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The number of microbes was analyzed in Balai Veteriner Lampung. The method in this research used completely randomized design. The treatments was consisted of basal ration (R0), basal diet + stater EM4 (R1), basal diet + EM4 starter culture (R2), and the basal diet + starter rumen fluid (R3). The results showed that the addition of various kind levels of starter indicated significant effect (P<0.05) to moisture, very significant effect (P<0.01) to crude fat, but indicated not significant effect (P>0.05) to crude fiber and BETN of silage. (Keywords: Silage, Rumen Fluid, EM4, Nutrition)